Conceptualizing Thriving: An Exploration of Students’ Perceptions of Positive Functioning Within Graduate Education - Coe-Nesbitt, Heather A.; Soleas, Eleftherios K.; Moucessian, Anoushka M.; Arghash, Nadia; Kutsyuruba, Benjamin (Frontiers in Education, 2021)
The current wellness crisis among graduate students calls on institutions of higher education to act and advocate for student thriving. While existing research on human thriving provides insight into how this experience of positive functioning can be understood across the lifespan, what it means to thrive within graduate programs—and by extension, how to support students in their ability to thrive within these programs—remains understudied. To address this gap in the literature, this study examined how graduate students describe and understand thriving within their programs of study. Findings indicate that graduate students conceptualize thriving as a complex and multi-dimensional construct involving both academic and non-academic components. The six overarching themes of achieving, engaging, connecting, balancing, enjoying, and being provide foundation for further exploration and insight into the ways that universities and post-secondary institutions can support students’ positive functioning.